The downregulation of genes encoding muscle proteins have a potential role in the development of scrotal hernia in pigs - Lorenzetti W.R.* (2024)
© The Author(s), under exclusive licence to Springer Nature B.V. 2024.Background: Testicular descent is a physiological process regulated by many factors. Eventually, disturbances in the embryological/fetal development path facilitate the occurrence of scrotal hernia, a congenital malformation characterized by the presence of intestinal portions within the scrotal sac due to the abnormal expansion of the inguinal ring. In pigs, some genes have been related to this anomaly, but the genetic mechanisms involved remain unclear. This study aimed to investigate the expression profile of a set of genes potentially involved with the manifestation of scrotal hernia in the inguinal ring tissue. Methods and results: Tissue samples from the inguinal ring/canal of normal and scrotal hernia-affected male pigs with approximately 30 days of age were used. Relative expression analysis was performed using qPCR to confirm the expression profile of 17 candidate genes previously identified in an RNA-Seq study. Among them, the Myosin heavy chain 1 (MYH1), Desmin (DES), and Troponin 1 (TNNI1) genes were differentially expressed between groups and had reduced levels of expression in the affected animals. These genes encode proteins involved in the formation of muscle tissue, which seems to be important for increasing the resistance of the inguinal ring to the abdominal pressure, which is essential to avoid the occurrence of scrotal hernia. Conclusions: The downregulation of muscular candidate genes in the inguinal tissue clarifies the genetic mechanisms involved with this anomaly in its primary site, providing useful information for developing strategies to control this malformation in pigs and other mammals.